Arabic Techno-Paper Poetry: Creative Justifications And Literary Features/ الشعر التكنو ورقي: المُسوّغات الإبداعيَّة والسّمات الأدبيَّة - Hiba Mohammed Mhidi; Harith Yaseen Shukur (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study seeks to uncover the most important creative justifications and literary characteristics of